(untitled) (Revista Argentina de Cirugía, 2026)
Hepatic artery aneurysms are rare. Expanding aneurysms should be suspected in case of symptoms and treatment is indicated. We report the case of a patient with a history of cardiovascular disease who sought medical care due to epigastric pain, hemodynamic instability and jaundice. The imaging tests showed the presence of an aneurysm of the common hepatic artery complicated with involvement of the origin of the proper hepatic artery and the gastroduodenal artery. The surgical approach could be changed due to presence of a “non-conventional” hepatic arterial variant with a right hepatic artery originating from the superior mesenteric artery in the computed tomography angiography as bypass surgery was not necessary. This case highlights the importance of determining the extent of the aneurysm in the preoperative period and the anatomy of the hepatic vessels to better plan the surgery, thus reducing morbidity and mortality of this disease.